Searching for SM-LIKE heavy new quarks at the LHC - Şahinsoy, Merve. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2015., 2015)
This thesis describes the search performed with the ATLAS detector for heavy quarks (denoted as Q) in the Q Q ! WqWq channel where one W boson decays leptonically and the other hadronically. Final state of this processes is four jets, one lepton and missing transverse energy. The analysis is based on an integrated luminosity of 20 fb{u100000}1 data collected during the 2012 from proton-proton collisions at a centre-of-mass energy of 8 TeV. No signi cant excess of events above the Standard Model expectation is observed and lower limit on the Q quark mass has been set at 519 GeV for electron channel and 475 GeV for muon channel with 95% con dence level.
Keywords: Higgs bosons.; Particles (Nuclear physics)